One polymer composition, various morphologies: the decisive influence of conditions on the polymerization-induced self-assembly (PISA) of N-acryloyl thiomorpholine. Issue 39 (6th October 2020) - Sobotta, Fabian H.; Kuchenbrod, Maren; Hoeppener, Stephanie; Brendel, Johannes C.
Abstract : Adaptation of solution morphologies for the same block copolymer by variation of conditions during the aqueous RAFT dispersion polymerization of N -acryloylthiomorpholine. Abstract : Polymerization-induced self-assembly (PISA) represents a powerful technique for the preparation of nanostructures comprising various morphologies. Herein, we demonstrate that the recently introduced monomer N -acryloylthiomorpholine (NAT) features a unique self-assembly behaviour during an aqueous PISA. The one-pot, aqueous RAFT dispersion polymerization starting from short poly( N -acryloylmorpholine) (PNAM) enables access to all common solution morphologies including spheres, worms, vesicles and lamellae, at very low molar masses (< 8 kDa). Moreover, all these structures can be obtained for the same polymer composition and size by the variation of the polymerization temperature and concentration of the monomer. This exceptional self-assembly behavior is associated with the combination of a high glass transition temperature, excellent water solubility of the monomer, and the early onset of aggregation during the polymerization, which stabilizes the morphology at different stages. This PISA system opens up new opportunities to reproducibly create versatile, functional nanostructures and enables an independent evaluation of morphology-property relationships, as it is exemplarily shown for the oxidative degradation of spherical and wormlike micelles, as well as vesicles.